Hubungan Lamanya Menderita Diabetes Melitus DenganTerjadinya Diabetic Peripheral Neuropathy (Dpn) PadaPasien Diabetes Mellitus Tipe 2 Di Grha DiabetikaSurakarta - Aghniya, Rofana, Dwi Rosella K.S, S.Fis., M.Fis., DIPL.CIDESCO (2017)
Diabetes mellitus is one of many metabolism disease which can be seen by hyperglycemia or high blood sugar due to the decrease of insulin secretion by beta cells in the pancreas or insulin function defect (insulin resistance). Diabetes mellitus leads to a chronic complications such as neuropathy (29,5%) and nephropathy (15,7%). Diabetic neuropathy is caused by a chronic hyperglycemia that increase the polyol pathway activity which affect the distraction of signal's transduction on nerve. Diabetic neuropathy is classified in to 4 type : Diabetic Peripheral Neuropathy (DPN), autonomic, proximal and focal diabetic neuropathy. Diabetic Peripheral Neuropathy 2 (DPN) is the most common neuropathy on patient with type 2 dm due to the damage of peripheral nerve on feet or hand. Purpose : to figure out the correlation between the duration of suffering from diabetes and the occurrence of Diabetic Peripheral Neuropathy (DPN) towards type 2 diabetes mellitus this study uses an observation research with cross sectional method. By using quota sampling technique, it obtains 100 people as the sample for this research. The sample assessed by Michigan Neuropathy Screening Instrument (MNSI) to diagnose DPN. It includes two separate assessments: Test A (a 15 items questions) and Test B (physical test including vibration test, ankle reflex test, monofilament test and inspections). For test A a score ≥7 means positive and for test B a score ≥ 2,5 means positive. Statistical trial uses Chi-Square test. From total 100 samples, 52 people (52%) are positively diagnosed DPN (11 people in low duration category, 22 moderate duration category and 19 in high duration category). The result of value after doing correlation test Chi-Square was Asymp.Sig = 0,0001. It's indicates that there is a correlation between the duration of suffering from diabetes mellitus and the occurrence of Diabetic Peripheral Neuropathy (DPN) with Odd ratio (OR) value 0,25 which means that the longer someone suffers from diabetes mellitus, the possibility of having DPN increase up to 25%. There is a significant correlation between the duration of suffering from diabetes and the occurrence of Diabetic Peripheral Neuropathy (DPN) towards type 2 diabetes mellitus patients in GRHA Diabetika Surakarta.